THE ROLE OF DIGITAL TOOLS IN ENHANCING VOCABULARY ACQUISITION FOR A2 LEARNERS - Davronbek Komiljonov (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: This article examines the effectiveness of digital tools in vocabulary acquisition for learners at the A2 level according to the Common European Framework of Reference for Languages (CEFR). Drawing on an extensive review of empirical and theoretical research, the study highlights the role of mobile applications, spaced repetition flashcards, multimedia resources such as captioned videos, game-based learning, and adaptive AI-driven platforms in facilitating vocabulary development. The results demonstrate that digital tools significantly improve vocabulary retention and learner motivation when properly integrated into pedagogical practices. The article emphasizes the necessity of teacher mediation, the importance of multimodal learning strategies, and the need for long-term empirical research with CEFR-specific participant samples. Recommendations for pedagogical practice and directions for future inquiry are provided.